Fintech and Islamic Finance: Literature Review and Research Agenda - Hasan, Rashedul; Hassan, Mohammad Kabir; Aliyu, Sirajo (International Journal of Islamic Economics and Finance (IJIEF), 2020)
Fintech revolution started with the introduction of credit cards in 1960 and have been revolutionized with blockchain technologies. Integration of Fintech based solution with Islamic finance has gained interest among academics. However, the lack of literature evidence on this issue has motivated us to conduct a systematic literature review on Islamic Fintech. We have identified fourteen documents relevant to the context of the study and conducted the content and thematic analysis. An extensive review of past literature allows us to identify Shari’ah compliance as one of the major challenges for the growth of Islamic fintech. In addition, we conclude that Islamic fintech might pose challenges for Islamic Financial Institutions (IFIs) in terms of operational efficiency, customer retention, transparency and accountability. We contribute by providing insights on the challenges faced by the Islamic finance industry toward integrating Fintech based solutions with reference to past studies and indicate areas for future studies that could reduce the gaps in Islamic Fintech literature.